2011
DOI: 10.1259/bjr/30591350
|View full text |Cite
|
Sign up to set email alerts
|

The value of diffusion-weighted MRI in the diagnosis of malignant and benign urinary bladder lesions

Abstract: Objectives: To investigate the role of diffusion-weighted MRI (DWI) in the diagnosis of urinary bladder (UB) tumours by means of measuring apparent diffusion coefficient (ADC) values. Methods: A total of 83 people aged between 18 and 86 years were included in the study: 63 patients with UB pathology (46 malignant, 17 benign) constituted the case group; 20 individuals without any UB pathology constituted the control group. DWI was applied to all individuals. The ADC values were measured based on the tissue of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
49
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 20 publications
5
49
2
Order By: Relevance
“…Because of this limitation, DW-MRI was previously only used for brain imaging until the development of fast MRI techniques. The development of echo planar imaging (EPI), one of the fast MRI techniques, eliminated the long imaging time of conventional sequences and the associated artifacts, thus making DW-MRI usable for abdominal examinations (8)(9)(10)(11).…”
Section: Discussionmentioning
confidence: 99%
“…Because of this limitation, DW-MRI was previously only used for brain imaging until the development of fast MRI techniques. The development of echo planar imaging (EPI), one of the fast MRI techniques, eliminated the long imaging time of conventional sequences and the associated artifacts, thus making DW-MRI usable for abdominal examinations (8)(9)(10)(11).…”
Section: Discussionmentioning
confidence: 99%
“…In the various studies, different approaches were used; most of them used both T2W and DWI [8] [10] [15], but some evaluated the sequences separately in identifying the tumor [7] [15]. The sensitivities and specificities in the present study are lower than those studies.…”
Section: Discussionmentioning
confidence: 73%
“…Of these, 27 studies were excluded after scanning their title and abstract and a further 192 studies were excluded for failing to meet our inclusion criteria after examining their full-text. Finally, 11 studies, with diagnostic trials published between 1998 and 2014, were enrolled into the final analysis [9,[22][23][24][25][26][27][28][29][30][31]. Among these 11 studies, five studies reported the diagnostic performance of DW-MRI in BC, including 243 BC patients with bladder lesions and 82 subjects with healthy bladder tissues,Eight studies investigated the diagnostic performance of DW-MRI in 747 MIBC patients with 259 MIBC lesions and 515 NMIBC lesions.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…In recent years, several MRI methods, in conjunction with conventional methods including computed tomography (CT), ultrasound and positron emission tomography (PET), are being used for routine radiodiagnostic applications [9]. Diffusion-weighted magnetic resonance imaging (DW-MRI) is a recent advancement in microstructural imaging modality, and is characterized within the context of functional MRI.…”
mentioning
confidence: 99%
See 1 more Smart Citation